Estimation and prediction metrics for adaptive maintenance effort of object-oriented systems. - Fioravanti, F. (IEEE Transactions on software engineering)
Many software systems built in recent years have been developed using object-oriented technology and, in some cases, they already need adaptive maintenance in order to satisfy market and customer needs. In most cases, the estimation and prediction of maintenance effort is performed with difficulty due to the lack of metrics and suitable models. In this paper, a model and metrics for estimation/prediction of adaptive maintenance effort are presented and compared with some other solutions taken from the literature. The model proposed can be used as a general approach for adopting well-known metrics (typically used for the estimation of development effort) for the estimation/prediction of adaptive maintenance effort. The model and metrics proposed have been validated against real data by using multilinear regression analysis. The validation has shown that several well-known metrics can be profitably employed for the estimation/prediction of maintenance effort